Negative emissions technologies and carbon capture and storage to achieve the Paris Agreement commitments. (2nd April 2018) - Haszeldine, R. Stuart; Flude, Stephanie; Johnson, Gareth; Scott, Vivian
Abstract : How will the global atmosphere and climate be protected? Achieving net-zero CO2 emissions will require carbon capture and storage (CCS) to reduce current GHG emission rates, and negative emissions technology (NET) to recapture previously emitted greenhouse gases. Delivering NET requires radical cost and regulatory innovation to impact on climate mitigation. Present NET exemplars are few, are at small-scale and not deployable within a decade, with the exception of rock weathering, or direct injection of CO2 into selected ocean water masses. To keep warming less than 2°C, bioenergy with CCS (BECCS) has been modelled but does not yet exist at industrial scale. CCS already exists in many forms and at low cost. However, CCS has no political drivers to enforce its deployment. We make a new analysis of all global CCS projects and model the build rate out to 2050, deducing this is 100 times too slow. Our projection to 2050 captures just 700 Mt CO2  yr −1, not the minimum 6000 Mt CO2  yr −1 required to meet the 2°C target. Hence new policies are needed to incentivize commercial CCS. A first urgent action for all countries is to commercially assess their CO2 storage. A second simple action is to assign a Certificate of CO2 Storage onto producers of fossil carbon, mandating a progressively increasing proportion of CO2 to be stored. No CCS means no 2°C. This article is part of the theme issue 'The Paris Agreement: understanding the physical and social challenges for a warming world of 1.5°C above pre-industrial levels'.